PROTECTION OF CITIZENS' RIGHTS IN THE ERA OF ARTIFICIAL INTELLIGENCE AND DIGITAL TRANSFORMATION - Hermansyah; Arik Darojat; Dedi Haryanto; Asep Sopian; Indah Nurlaelah (SAHUR Journal, 2026)
The rapid development of Artificial Intelligence and digital technologies has brought significant changes in how governments deliver public services and how people live their daily lives. These innovations offer various advantages, including greater efficiency, transparency, and easier access to services. However, alongside these benefits, there are also emerging challenges, particularly in relation to the protection of citizens’ rights. Threats such as personal data breaches, the potential use of unfair or biased algorithms, and the lack of strong legal guarantees for digital privacy and security cannot be overlooked. This highlights the crucial role of the state in ensuring that technological progress remains aligned with the principles of human rights. This study aims to examine the forms of legal protection for citizens’ rights within the context of Artificial Intelligence and digital transformation, while also identifying key challenges and possible solutions. The research adopts a normative juridical approach, utilizing both statutory and conceptual frameworks. The data are collected from various relevant legal sources and analyzed qualitatively. The findings indicate that the protection of citizens’ rights in the digital era still faces several obstacles. Existing regulations have not fully kept pace with rapid technological advancements, oversight mechanisms remain suboptimal, and the level of public digital literacy is still relatively low. Therefore, more focused efforts are needed, such as strengthening legal regulations, enhancing transparency in the use of technology, and expanding public education. These measures are essential to create a digital ecosystem that is safe, fair, and capable of protecting the rights of every citizen.